Manure availability in relation to sustainable food crop production in semi-arid West Africa: Evidence from Niger - Williams, Timothy O.; Powell, J.M.; Fernández Rivera, S. (1995)
Despite its vital role in supporting crop production, a key question that has often been posed is whether sufficient amounts of manure are available to permit adequate food production and improvement of soil quality on a long-term basis. While this question can be addressed at a regional, national, village or household level, this paper examines it at the household, village, and national level using data from Niger. Its aim is to assess the adequacy of available manure for food crop production, and to determine the role that manure and other soil amendments can play in the future intensification of agricultural production in SAWA. A three-step approach was adopted for this study. First, the amount of manure required to replace nutrients taken up from croplands at various yield levels was estimated. Second, the number of animals (and the feed resources) needed to produce this level of manure was estimated and compared with the level of livestock holdings found in village and national studies. Third, the gap in manure supply was calculated and the amount of inorganic fertilizer needed to meet the manure shortfall was determined.